An RNA-seq primer for pulmonologists. Issue 1 (23rd January 2020) - Chu, Sarah G.; Poli De Frias, Sergio; Raby, Benjamin A.; Rosas, Ivan O.
RNA sequencing is a powerful tool for high-resolution transcriptomic analysis and can be leveraged to better understand the molecular underpinnings of diverse lung diseases http://bit.ly/2mqBnl4